Efeito da violência intrafamiliar sobre o pensamento contrafactual de mulheres - Justino, Florença Lucia Coelho (Universidade Federal de São Carlos, 2014)
Thinking about what have happened or thinking counterfactually is an important type of imagination thinking and may be defined as thoughts about alternatives to something that have been experienced in order to change the sequence of events or modify what happened with the purpose of reaching a different outcome. Considering that counterfactual thinking is insert in the imaginative function and recognizing the importance of imaginative thinking as a significant form of adaptation to reality, which can be achieve through the modification of elements, the aims of this work are: elaborate and evaluate a technique for evaluation of counterfactual thinking in adults (Study 1) and assess the extent to which victimization as a traumatic experience influences the generation of specific types of counterfactual thinking, ensuring if there will be differences in counterfactual thinking generated by women victims of violence and women which do not (Study 2). The material was composed by five stories adapted from newspapers and magazines articles followed by questions and four modification alternatives. Considering the high concordance among judges at the end of the fourth evaluation, the material produced is adequate to assess counterfactual thinking in adults. The material developed was presented to 16 women victims of violent and to 20 not victimized. Content analysis and frequency of categories were conducted to analyze the free and direct report modification responses. Regarding the modification alternatives, the frequency of responses and the means were calculated for both groups. The Student s t-test was conducted to verify the statistics meaning of the mean s differences. Most of the thoughts were classified as upward, subtractive, self referent and referring to the action aspect. Altogether, the pattern of thoughts were similar in both groups. The first story was discriminative once it was the one from which the differences between groups were revealed.
Effects of violence in counterfactual thinking of women
Keywords: Imaginação; Modificação da realidade; Violência; Imagination; Modification of reality; Violence against women; CIENCIAS HUMANAS::PSICOLOGIA